2009
DOI: 10.1121/1.3086272
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory investigation of the acoustic response of seagrass tissue in the frequency band 0.5–2.5 kHz

Abstract: Previous in situ investigations of seagrass have revealed acoustic phenomena that depend on plant density, tissue gas content, and free bubbles produced by photosynthetic activity, but corresponding predictive models that could be used to optimize acoustic remote sensing, shallow water sonar, and mine hunting applications have not appeared. To begin to address this deficiency, low frequency (0.5-2.5 kHz) acoustic laboratory experiments were conducted on three freshly collected Texas Gulf Coast seagrass species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 11 publications
3
25
1
1
Order By: Relevance
“…Cores were collected to provide measurements of macroscopic biomass, bulk sediment density, and mean grain size for correlation with the acoustic data. These preliminary results indicate that seagrass can have profound effects on the sound speed and attenuation not only within the water column, as noted by previous work, 3,4,[7][8][9] but also within the sediment beneath the seagrass. Future work will include investigations of dispersion, shear wave propagation within the sediment, and differences between various seagrass species.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Cores were collected to provide measurements of macroscopic biomass, bulk sediment density, and mean grain size for correlation with the acoustic data. These preliminary results indicate that seagrass can have profound effects on the sound speed and attenuation not only within the water column, as noted by previous work, 3,4,[7][8][9] but also within the sediment beneath the seagrass. Future work will include investigations of dispersion, shear wave propagation within the sediment, and differences between various seagrass species.…”
Section: Discussionsupporting
confidence: 62%
“…The density and elastic moduli of the plants themselves can also potentially affect long-range acoustic propagation by altering the effective material properties at the water-sediment interface and within the seabed when seagrass meadows are ubiquitous in the environment. 8,9 Whereas previous studies on the acoustic properties of seagrass have focused on sound propagation and backscatter in the water column, little prior work has focused on measurement of acoustic properties below the water-sediment interface where the plant rhizome and root systems exist. This letter reports preliminary in situ measurements of sound speed and attenuation in a bed of Thalassia testudinum in the water column, in the canopy, and in the sediment beneath the seagrass.…”
Section: Introductionmentioning
confidence: 99%
“…The free gas bubbles increase the acoustic compressibility of the seawater (Hermand, 2004), whereas an increase of internal pressurization should give rise to a decrease of acoustic compressibility. However, leaf morphology and the total biomass also influence acoustic compressibility of the seagrass and various patterns were observed among seagrasses (Wilson and Dunton, 2009); (Wilson et al, 2010(Wilson et al, , 2012. Until now, it was not possible to find a model that allows to quantitatively describe the acoustic response of seagrasses.…”
Section: Discussionmentioning
confidence: 99%
“…At frequencies well below the bubbles resonance frequency, both factors influence the acoustic compressibility and, thus, the effective sound speed of the medium (Hermand et al, 2000); (Wilson and Dunton, 2009); (Wilson et al, 2010(Wilson et al, , 2012. Attempts to quantify the effective sound speed of the seagrass environment through an effective medium model, such as Wood's equation (Wilson et al, 2010), have been shown to be inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn benefits sonar operation and acoustic communication in shallow water, and will increase the accuracy of acoustically-based fisheries surveys. This study will utilize both one-and three-dimensional acoustic resonator techniques, previously developed by the author under ONR [1,2] and industry [3] sponsorship, and free-field measurement techniques to study the low-frequency (50-10000 Hz) acoustics of collections of model fish, large (≈10 cm diameter) encapsulated bubbles and schools of real fish in the laboratory.…”
Section: Long-term Goalsmentioning
confidence: 99%